A super-stretchable, self-healing and injectable supramolecular hydrogel constructed by a host–guest crosslinker. (6th May 2020) - Zhou, Yang; Zhang, Yuanhao; Dai, Zhaobo; Jiang, Fang; Tian, Jia; Zhang, Weian
Abstract : Supramolecular hydrogels based on host–guest interactions have drawn considerable attention due to their unique properties and promising applications. Abstract : Supramolecular hydrogels based on host–guest interactions have drawn considerable attention due to their unique properties and promising applications. However, it is still a great challenge to construct supramolecular hydrogels that simultaneously achieve mechanical strength, processability, and biocompatibility. Herein, we present a rational design of a "supramolecular crosslinker" approach to fabricate a new host–guest hydrogel with super-stretchability, self-healing, and injectable properties and excellent biocompatibility. The star-shaped supramolecular crosslinker is formed by the host–guest interactions between octa-cyclodextrin polyhedral oligomeric silsesquioxane (OCDPOSS) and acrylamide-modified adamantane (Ad-AAm). Supramolecular hydrogels can be briefly prepared by UV-initiated copolymerization of acrylamide and supramolecular crosslinkers. Supramolecular hydrogels present impressive mechanical properties due to rigid POSS as the core of the supramolecular crosslinker. Moreover, multivalent host–guest interactions improve the ductility, rapid self-healing and injectable ability of these hydrogels. Simultaneously, these supramolecular hydrogels possess good biocompatibility and can be utilized as carriers for the sustained release of hydrophobic drugs. Thus, such supramolecular hydrogels will have potential applications for tissue engineering and drug delivery systems.